Moderation Firm Size to Intellectual Capital, Commissioner Independent, Sales Growth And Firm Value - Margie, Lyandra Aisyah; Manurung, Adler Haymans; Buchdadi, Agung Dharmawan; Yusuf, Muhammad (AGUSPATI RESEARCH INSTITUTA, 2024)
The aim of this research is to examine the influence of intellectual capital, independent commissioners and sales growth on firm value with firm size as a moderating variable. The population used is property & real estate sub-sector companies listed on the IDX in 2017-2022. The sample was selected using the purposive sampling method. The results of data processing carried out by researchers were tested using moderated regression analysis (MRA) with the IBM SPSS Statistics Version 25 application. The research results showed that independent commissioners had a significant negative effect on firm value, while intellectual capital and sales growth did not have a significant effect on firm value. Firm size as a significant moderating variable weakens the relationship between independent commissioners and firm value. Meanwhile, firm size is unable to moderate the influence of intellectual capital and sales growth on firm value.